Attempted conservative treatment in endometrial carcinoma - Stanosz, Stanisław (Contemporary Oncology/Współczesna Onkologia, 2008)
Endometrial carcinoma appears not only in the early postmenopausal and menopausal period, but also in young women. Aim of the study: To assess the effectiveness of sequential treatment of menstrual cycle disorders in young women with primary uterus carcinoma zero degree. Material and methods: The exam included 5 women, aged 30.8±4.2, with menstrual cycle disorders, primary infertility and ductal carcinoma of mucous membrane of uterus. After assessment of sex hormone concentration and histopathological exams in menstrual disorders of women, supplement of oestriol, progesterone, bromocriptine and metformin was applied. Biochemical and histopathological exams were performed every 6 months for 2 years. Results: After 6 months of pharmacological treatment, menstrual cycles were normalized with physiological mucous membrane of uterus, without carcinoma structure. During 15 years of observation the health status of women was good. Four became pregnant and gave birth to healthy children. Conclusions: 1. In young women carcinoma of 0 degree could be an indication for pharmacological treatment. 2. Pharmacological treatment should be monitored via sex hormone concentration and histopathological exams of mucous membrane of uterus every 6 months for 2 years.